Діяльність І. І. Петрункевича у Борзнянському повітовому земському зібранні (1868 –1879) - Котельницький, Н. (Сiверянський лiтопис, 2018)
Стаття присвячена діяльності І. І. Петрункевича у Борзнянському повітовому
земстві. Особлива увага приділена реформаторським ініціативам політика у галузі
народної освіти та медицини. Висвітлені прогресивні пропозиції діяча у сфері економіки,
розвитку судової системи у провінції, розмежуванні компетенції земських установ і
губернської бюрократії. Статья посвящена деятельности И. И. Петрункевича в Борзнянском уездном
земстве. Особое внимание уделено реформаторским инициативам политика в сфере
народного просвещения и медицины. Показаны прогрессивные предложения деятеля в
сфере экономики, развития судебной системы в провинции, разграничении компетенции
земских учреждений и губернской бюрократии. In a publication the major constituents of activity of I. I. Petrunkevich in Borzna zemstvo are
investigating. The special attention is spared to the reformative initiatives of politician in area
of folk medicine and education. Shows examples of philanthropic and sponsorship activities of
I. Petrunkevich in education.The progressive suggestions of politician in the field of economics,
fiscal policy, development of the judicial system in provinces, delimitations of jurisdiction
of zemstvo establishments and province bureaucracy are lighted up.To light up innovation
I.Petrunkevich into sphere reforms army state, pharmacology and dispensing chemists.
Considerable interest to call to create personal initiatives politics zemstvo statistical service
as agency along to reveal corruption in society. As a result of the research a conclusion about
modern, reformist character of Petrunkevich’s activity, directed on capitalist modernization,
to the vital functions of province is formed.